Depression, anxiety, and stress symptoms among labor force participants in Iceland: The effects of gender, parental status, financial strain and family member support - Valdís Ósk Jónsdóttir 1993- (2020)
This research examined the relationship between gender, parenting, financial strain and family member support and depression, anxiety, and stress symptoms among labor force participants in Iceland. In particular, the aim was to examine whether working females experienced higher levels of financial strain, family member support and average symptoms of depression, anxiety, or stress, compared to working males. Furthermore, it was to investigate whether financial strain, family member support, and parental status were independent predictors of symptoms of depression, anxiety, and stress, and to test if these variables were stronger predictors of depression, anxiety, and stress symptoms for females than males. The study is based on data from the survey “Research on mental health of men and women in Iceland”, using responses from 518 labor force participants between the ages of 18 and 66 years (Mage= 45.2; SDage = 15.2). The findings demonstrated that female labor force participants reported higher mean levels of anxiety and stress symptoms than male participants, but there was no gender difference found for depression symptoms. Findings also showed that having low family member support, not being a parent and having high financial strain were independent predictors of high levels of depression, anxiety and stress symptoms, with family member support and parental status being stronger predictors of anxiety symptoms for females than males. The results suggest that family member support is an important factor for mental health among labor force participants in Iceland.